Optimal tuning of fractional order sliding mode controller for PMSM speed using neural network with reinforcement learning - Fardila Mohd Zaihidee (Tanjung Malim, 2023)
Optimal tuning of fractional order sliding mode controller for PMSM speed using neural network with reinforcement learning by Fardila Mohd Zaihidee